Rancang Bangun Transmitter dan Receiver untuk Sistem Komunikasi Akustik Bawah Air - Henry Manik; Susilohadi Susilohadi; Billi R Kusumah (Universitas Syiah Kuala, 2019)
Since 2016 acoustic detection technology for marine resources had been developed which was relatively simple and sophisticated, namely Ocean Acoustic Waveguide Remote Sensing. The technology was useful for monitoring and quantifying underwater targets such as marine resources and the environment that can be conducted continuously, sustainable, in situ, real-time, and low cost. This research had designed an Ocean Acoustic Remote Sensing technology instrument to detect signal propagation range. The step taken in this research was to build an acoustic device system such as transmitter and receiver based on TR-103 transmitting transducer sensor and Benthos Aq-1 receiving transducer. Based on the experiment results, the transmitter and receiver designed were confrmed with the measured piezoelectric quantity specifcations. The results at open ocean in the Thousand Islands showed the detection range of transmitter signal propagation to the receiver was 100 m.